Per un superamento delle ‘due culture’. I nuovi albi illustrati di divulgazione per l’infanzia e l’intreccio possibile e fecondo tra scienza e arte - Grilli, Giorgia (Studi sulla Formazione/Open Journal of Education, 2019)
In our modern world, there is a clash between scientific research and the humanities, between the exact, experimental, objective knowledge offered us by the natural sciences and the unprovable but touching insights, enlightenments, and awareness acquired through literature, poetry, art, philosophy, and our sensitive, emotional immersion in the world. The two kinds of knowledge are usually kept separate or deemed opposite in our Western culture, but they come together in an illuminating way within and thanks to a new genre of picturebook for children that has been spreading at an international level over the last decade and demands critical analysis.